Global, regional, and national burden of iodine deficiency for women of reproductive age, 1990–2021: a systematic analysis based on the Global Burden of Disease Study 2021 - Wang, Taotao; Tong, Jingmin; Liu, Yuzhou; Liu, Yanqiu; Xu, Hui; Liu, Yang (Frontiers in Nutrition, 2025)
ObjectiveThis study aims to assess the global, regional, and national burden of iodine deficiency among women of reproductive age (WRA) from 1990 to 2021.MethodsUtilizing data from the Global Burden of Disease Study 2021, this study reports age-standardized rates per 100,000 population and average annual percentage changes (AAPCs) in incidence, prevalence, and years lived with disability (YLD) of iodine deficiency among WRA, facilitating a comparative analysis of the burden across regions and nations. Moreover, Joinpoint analysis was utilized to assess temporal trends, the slope index and concentration index of inequality were used to assess the health inequality across countries. The Bayesian age-period-cohort model was employed to forecast the burden up to 2044.ResultsA notable upward trend in the age-standardized incidence rate (ASIR) of iodine deficiency among WRA was observed globally from 1990 to 2021, and this trend is projected to remain relatively stable between 2021 and 2030. The global ASIR increase from 171.3 per 100,000 population (95% CI 122.8, 228.2) in 1990 to 193.6 (95% CI 141.7, 253.2) in 2021 with an AAPC at 0.36 (95% CI 0.26, 0.47). Moreover, the global age-standardized prevalence rate (ASPR) and age-standardized YLD rate (ASYR) demonstrated decreased trend with the AAPC of −0.31 (−0.35, −0.27) and −1.05 (−1.19, −0.92), respectively. In 2021, countries with low sociodemographic index (SDI) exhibited the highest iodine deficiency burden. The highest burden of iodine deficiency was observed in Central Sub-Saharan Africa, while East Asia exhibited the highest increase in ASIR, ASPR and ASYR. Women of 20–24 years showed the highest increase in the age specific incidence rate globally. The significant absolute and relative health inequality was also observed and the gap has been narrowed.ConclusionsOver the past three decades, there has been an overall upward trend in the ASIR of iodine deficiency among WRA globally. Health inequalities related to iodine deficiency was still prominent across countries. Iodine deficiency among WRA remains a significant public health issue. It is crucial to prioritize the development of effective, targeted strategies and implement monitoring mechanisms to enhance the iodine levels among WRA.